Strengthening community engagement through SAA programme - Abd Karim, Nur Qurratul Nusrah; Mohd Fauzie, Nur Siti Khadeejah; Karim, Fatimah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia, 2025)
Held on 13 December 2025, the programme was organised by the Secretariat of Fiqh and Usul al-Fiqh (Session 2024/2025) and involved students from RKFQ 2313: Fiqh al-Usrah (Sections 1, 2, and 3) and RKFQ 4315: Qadaya Fiqhiyyah Muʿasirah. More than 100 members of the local community took part, transforming the mosque into a shared learning space where theory met real-life experience.